Hospital Financial Burden of Surgical Procedures for Periprosthetic Total Hip Arthroplasty Infection - Jesus M. Villa, MD; Tejbir S. Pannu, MD, MS; Robert B. Eysler, BA; Vivek Singh, MD, MPH; Alison K. Klika, MS; Carlos A. Higuera, MD (Arthroplasty Today)
Background: For reimbursement purposes, current coding fails to reflect the true complexity and resource utilization of hospital encounters for surgeries performed to treat periprosthetic total hip arthroplasty (THA) infection. Therefore, when compared to aseptic revisions, we sought to determine (1) Is length of stay (LOS) longer for septic surgeries? (2) Are septic procedures more expensive? and (3) How do different surgical procedures for infection compare with aseptic revisions on hospital LOS and charges? Methods: Retrospective chart review of 596 unilateral THA reoperations (473 patients) performed at a single institution (January 2015 to November 2020). Demographics, professional (ie, physicians), and technical (ie, room, implants) hospital charges per case were compared between 6 different surgery types: (1) aseptic revision (control; n = 364); (2) debridement, antibiotics, and implant retention (n = 11); (3) explantation (n = 145); (4) spacer exchange (n = 7); (5) 2-stage reimplantation (n = 59); and (6) 1-stage reimplantation (n = 10). Results: Overall, septic surgeries (n = 232) had longer LOS (mean 6.3 vs 3.3 days, P < .001) and 43% higher total charges (P < .001), vs aseptic revisions. Particularly, explantations had longer LOS (7.1 vs 3.3 days) and 56% higher total charges (both P < .001). When compared to aseptic revisions, proportional total charges for septic procedures were debridement, antibiotics, and implant retention +29%, P = .4; explantation +56%, P < .001; spacer exchange +69%, P = .008; 2-stage reimplantation +11%, P = .659; and 1-stage reimplantation +46%, P = .06. Conclusions: Some surgical procedures performed to treat periprosthetic THA infection are associated with longer LOS and significantly higher hospital charges when compared to aseptic revisions. Reimbursement adjustment is needed as current coding for septic reoperations does not reflect actual hospital resource consumption and this situation may limit access to patient care.